Country Partnership Framework for the People's Republic of China for the Period FY2020-2025 - World Bank Group (World Bank, Washington, DC, 2019)
Following four decades of high growth and poverty reduction, China has entered a new stage of development. Governance and institutional reforms are at the core of addressing China’s remaining development challenges. The China-World Bank Group (WBG) relationship, which will complete 40 years in 2020, is also entering a new phase. To implement this approach, new WBG financing will be subject to selectivity criteria, and IBRD financing will gradually decline. IFC will apply a rigorous additionality assessment to its program. This Country Partnership Framework will focus on three areas of engagement: advancing market and fiscal reforms; promoting greener growth; and sharing the benefits of growth. Cooperating on global knowledge and development is a cross-cutting theme.